SYNTHESIS OF 5,7-DIHYDROXY-3’,4’-DIMETHOXYISOFLAVON FROM EUGENOL - Andi Hairil Alimuddin; Sabirin Matsjeh; Chairil Anwar; Mustofa Mustofa (Universitas Gadjah Mada, 2011)
Synthesis of 5,7-dihydroxy-3',4'-dimethoxyisoflavone from eugenol as isolated product of clove leaves oil had been done. Eugenol was firstly converted into 3,4-dimethoxybenzyl cyanide via several stages of reaction. Hoeben-Hoesch reaction of 3,4-dimethoxybenzyl cyanide with phloroglucin produced 3,4-dimethoxybenzyl-2',4',6'-trihydroxyphenyl ketone (deoxybenzoin intermediate) in 58% yield. Eventually, cyclization of the intermediate with reagents of BF3.OEt2/DMF/POCl3 yielded 5,7-dihydroxy-3',4'-isoflavone in 88% yield.